Ácido giberélico na indução e qualidade do florescimento de orquídea Phalaenopsis ‘White Dream’ - Cardoso, Jean Carlos; Ono, Elizabeth Orika [UNESP]; Rodrigues, João Domingos [UNESP] (Lepidus Tecnologia, 2012)
The control of flowering is essential in the cultivation of flowers to the rapid commercialization and cost reduction. We evaluated the use of Gibberellic Acid (GA3) on floral induction and quality of flowering of adult plants of Phalaenopsis hybrid. It was test five concentrations of GA3: 0, 125, 250, 500 and 1.000mg L-1 applied twice or four times with seven days of interval. This was made by foliar pulverization in the months of November and December. Promising results for induction of flowering happened at a concentration of 125 mg L-1 GA3, applied for twice in Phalaenopsis plants, and with 83% of flowering plants. The number of flowers increased with increasing doses of GA3, until the concentration of 1.000 mg L-1 applied by twice, and without lost of flowers quality until 500mg L-1. The use of four applications of GA3 and the consequent elevation of concentration of the growth regulator in treated plants, caused reduction of inflorescences and flowers quality.

No cultivo de flores, o controle da floração é fator fundamental para comercialização rápida e com redução de custos. Foi avaliada a utilização do ácido giberélico (GA3) na indução floral e qualidade do florescimento de plantas adultas de Phalaenopsis híbrido. Foram testadas 5 concentrações de GA3 de 0, 125, 250, 500 e 1000 mg L-1 em 2 ou 4 pulverizações com intervalos de 7 dias, feitas via foliar nos meses de novembro e dezembro. Resultados promissores para a indução do florescimento ocorreram com a concentração de 125 mg L-1 de GA3, pulverizado por 2 vezes em plantas de Phalaenopsis, com 83% das plantas floridas. O número de flores aumentou com o incremento das doses de GA3 até a concentração de 1.000 mg L-1 em 2 pulverizações, sem diminuição da qualidade das flores até a concentração de 500mg L-1. Já o uso de 4 aplicações de GA3 e o consequente aumento das concentrações de aplicação do regulador vegetal nas plantas ocasionaram diminuição da qualidade das inflorescências e flores obtidas.
Gibberellic Acid (GA3) on flowering induction and quality of Phalaenopsis orchid
Keywords: Phalaenopsis; Ornamental plant; Growth regulators; Flowers; Phalaenopsis; Planta ornamental; Regulador vegetal; Flores